Okinawa : Two Postwar Novellas by Ōshiro Tatsuhiro and Higashi Mineo - Higashi, Mineo, 1938-; Ōshiro, Tatsuhiro, 1925-; Rabson, Steve, 1943- (Japan research monograph, 2021)
Half a century after the clash of Japanese and American forces devastated Okinawa in the spring of 1945, wide areas of Japan's southernmost prefecture remain an armed bastion. Although U.S. military rule in Okinawa ended in 1972, airfields, artillery ranges, ammunition depots, infantry training grounds, and other military installations still occupy large areas of the prefecture. People in Okinawa continue to protest the shortages of land, daily disruptions, and not infrequent dangers associated with this vast military presence. At a time of heightened controversy among Japanese and American scholars looking back on the occupation of Japan, this book (corrected and updated 1996) grew out of a conviction that works of literature often provide the best means for understanding how people live in unusual circumstances. The novellas translated here--Oshiro Tatsuhiro's "Cocktail Party" ("Kakuteru pati") and Higashi Mineo's "Child of Okinawa" ("Okinawa no shonen")--each won the coveted Akutagawa Prize for fiction for their authors. Although the novellas differ sharply in tone and form, both are first-person narratives of individual protagonists whose lives are profoundly affected by the U.S. occupation and military presence. The novellas are presented here in translation together with an introduction providing historical background and a concluding essay that compares and evaluates them. The introduction is intended to supply information that will help the reader understand specific points in the stories. For both essays, the author has drawn on Japanese and English-language sources including materials collected in Okinawa during eight months of a 1967-68 overseas tour in the U.S. Army and on subsequent visits to the island.